AESTHETIC AND SPIRITUAL DIMENSIONS OF MANIPURI RAAS LEELA: AN INTERDISCIPLINARY STUDY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The profound intertwining of theatrical art and mythology within Manipuri culture, emphasizing the significant contributions of King Bhagyachandra in shaping the Manipuri Raas Leela. Rooted in the Natya Shastra, the comprehensive ancient Indian treatise on performing arts, the study explores how Raas Leela integrates gesture, song, music, dance, and stagecraft to embody the aesthetic and philosophical ideals of Indian classical arts. Bhagyachandra's multifaceted role as a spiritual devotee, administrator, and artist is highlighted, particularly his innovative blending of Vaishnav philosophy with artistic expression to create Raas Leela as a path to spiritual salvation. The paper examines the philosophical, theatrical, cultural, and anthropological dimensions of Raas Leela, revealing its deep devotional spirit and unique characteristics within the broader artistic traditions of the region. It addresses the gap in detailed philosophical and technical analysis of Manipuri art forms, presenting a new approach for contemporary audiences. The study underscores the enduring relevance of Raas Leela, emphasizing its aesthetic values, production design, and spiritual aspects. By bridging traditional teachings and contemporary interpretations, this research fosters a deeper understanding and appreciation of Manipuri Raas Leela, celebrating its rich heritage and inviting further scholarly inquiry. This article delves into the unique aspects of Manipuri Raas Leela, tracing its roots and exploring its cultural, philosophical, and aesthetic dimensions.